Analysis of Traffic Accident-Related Facial Trauma. Issue 7 (October 2016) - Choi, Su Hyun; Gu, Ja Hea; Kang, Dong Hee
Abstract : Abstract: The consequences of facial trauma remain of great significance both functionally and esthetically. Traffic accident-related facial trauma is a frequent and significant cause of maxillofacial injury. The purpose of this study was to determine the natural history of traffic accident-related facial injuries in 846 patients over a 10-year period at a regional emergency center. The authors report a retrospective study of 846 patients with facial trauma from traffic accidents. The medical records of these patients were reviewed and analyzed to determine clinical characteristics, treatments, and outcomes of traffic accident-related facial trauma. In total, 687 of the 846 patients (81.2%) had fractures of the face, and nasal bone fractures were the most common followed by zygomatic complex fractures, blow-out fractures, and maxilla fractures. About 51.2% patients had open wounds on the face, such as lacerations, abrasions, skin or soft tissue defects, and friction burns. Only 7.4% of patients were treated conservatively and the others underwent repair or closed and open reduction. The complication rate was 46.3%, and scars were the most common followed by nose-related complication, hypoesthesia, and eyelid deformities. In addition, 47.6% of complication patients underwent secondary operations. Almost 15% of drivers were drunk, and about 8.7% were confessed drowsy during drive. Almost 30% of pedestrians were hit when they jaywalked across the street. Epidemiological data regarding traffic accident-related facial trauma are important and useful not only for decisions about patient care and developing optimal treatment regimens but to develop new methods to prevent injuries.